Diethylphosphonate-containing aminoacyl-adenosine analog as inhibitor of bacterial tRNA-dependent transamidase - Sangsuwan, Withsakorn; Boonkerd, Anon; Na Ayutthaya, Chawarat Isarangkool; Aonbangkhen, Chanat; Chuawong, Pitak (Agriculture and Natural Resources, 2024)
Importance of the work: The inhibitory activity of a transition state mimic of a bacterial tRNA-dependent transamidase could help in the control of many bacterial pathogens. Objectives: To design, synthesize and test the inhibitory activity of a transition state mimic of a bacterial tRNA-dependent transamidase. Materials & Methods: An aminoacyl-adenosine analog was synthesized and evaluated for its inhibitory activity against GatCAB, a tRNA-dependent transamidase. The saturation transfer difference nuclear magnetic resonance (STD NMR) experiments revealed binding epitopes. The disc diffusion method was conducted to test antibacterial properties, with molecular docking simulations elucidating the binding mode of the compound. Results: Compound 1, a non-hydrolyzable aminoacyl-adenosine analog featuring the sulfone and diethylphosphonate groups, was synthesized from 3-deoxy-3-aminoadenosine and NHCbz-L-cysteine. The synthesized compound retarded the transamidation rate of GatCAB by approximately 30%. In addition, the STD NMR analysis indicated binding epitopes of compound 1, highlighting interactions involving the hydrogens in the diethylphosphonate, anomeric position and the adenine ring. Molecular docking simulations further elucidated the binding mode of compound 1 at the GatB transamidation site. Nonetheless, compound 1 did not exhibit in vivo antibacterial effects against Pseudomonas aeruginosa, Staphylococcus aureus or Bacillus subtilis, presumably due to cell permeability issues. Main finding: The inhibition was highlighted of the tRNA-dependent transamidase, a novel target for antimicrobial development. Further structural modification to enhance membrane permeation could provide an antibacterial agent with a novel mechanism of action.